Assessment of profitability and efficiency analysis of watermelon (Citrullus lanatus) value chain in Yobe State, Nigeria - Aminu Abdulrahim Olayinka; Saadu Lawan (goodwood publishing, 2023)
Purpose: An imperative step in enhancing investment returns for watermelon producers and marketers is to comprehensively analyze the watermelon value chain. This evaluation was recently conducted in Yobe State, Nigeria, during the period spanning from July to August 2023. Research methodology: The data acquisition process involved the administration of a questionnaire that facilitated the gathering of information from 540 participants across various roles within the value chain, encompassing producers, wholesalers, and retailers operating within the study's geographic scope. Results: The findings of this investigation illuminate the prevalent utilization of urban marketing channels by watermelon marketers, and it is noteworthy that approximately half of these marketers engage in their marketing endeavors within urban markets such as Kano, Kaduna, and Abuja. Notably, the study underscores the substantial impact of transportation costs on both the pricing and net marketing returns associated with watermelons. A significant proportion of these marketers were motivated primarily by the pursuit of sustainable livelihoods, while the allure of profitability drove others. However, a critical challenge encountered in the watermelon marketing domain pertains to the accessibility of credit facilities, which affects nearly 90% of the stakeholders involved in the value chain. Additionally, other constraints exerted relatively minor effects on marketers' activities and outcomes. Limitations: This study was limited to data from 460 participants involved in various stages of the watermelon value chain in the study area from July to August 2023. Contribution: This study can aid different actors in the watermelon value chain when making investment decisions.